Model Extraction of Legacy C Code in SCCharts - Smyth, Steven; Lenga, Stephan; von Hanxleden, Reinhard (Electronic Communications of the EASST, 2018)
With increasing volumes of developed software and steadily growing complexity of these systems, software engineers struggle to manually maintain the vast amount of legacy code. Therefore, it is of interest to create a system which supports the documentation, maintenance, and reusability of software and its legacy code. The approach presented here automatically derives SCCharts models out of C code. These models can be used as visual documentation. By applying focus and context methods important parts of the model can be highlighted and may grant a better understanding of the overall software. Additionally, the models can also be used as a source to create new state-of-the-art code for various languages and platforms, such as C code or VHDL, using automatic code generators.